ORGANIZATION OF COMMUNICATION OF A MOTORIZED RIFLE PLATOON AND RULES FOR CONDUCTING RADIO COMMUNICATIONS - Raxmetov Quatbek Tal'gat o'g'li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article provides information on organization of communication of a motorized rifle platoon and rules for conducting radio communications